Response to the Variation of Clay Minerals During ASP Flooding in the Saertu Oilfield in the Songliao Basin - Yingjie, Liang; Wenfu, Liang; Wang, He; Zian, Li (Frontiers in Earth Science, 2021)
In this paper, the variation of clay minerals and their influence on reservoir physical properties and residual oil before and after ASP flooding are analyzed. The results show that the total amount of clay minerals in reservoirs decreases after ASP flooding in the ultra-high-water-cut-stage reservoirs of the Naner Zone in the Saertu Oilfield, Songliao Basin. Therein, the illite content reduces, while the content of illite smectite mixed-layer and chlorite increases. The content of kaolinite varies greatly. The content of kaolinite decreases in some samples, while it increases in other samples. The clay minerals block the pore throat after ASP flooding. As a result, the pore structure coefficient and the seepage tortuosity increase, the primary intergranular pore throat shrinks, and the pore–throat coordination number decreases. Nevertheless, the dissolution of clay minerals reduces the pore–throat ratio and increases porosity and permeability. The variation of clay minerals after ASP flooding not only intensifies the reservoir heterogeneity but also affects the formation and distribution of residual oil. The residual oil of the oil–clay mixed adsorption state is a newly formed residual oil type related to clay, which accounts for 44.2% of the total residual oil reserves, so it is the main occurrence form of the oil in reservoirs after ASP flooding. Therefore, the exploitation of this type of residual oil has great significance to enhance the oil recovery in ultra-high-water-cut-stage reservoirs.